PENGEMBANGAN MODEL ANALISIS SPASIAL UNTUK MENSIMULASIKAN RESPON HIDROLOGI - Asep Denih; Ema Kurnia; Umar Mansyur (Ilmu Komputer, FMIPA, Universitas Pakuan, 2020)
Urban expansion is a major driving force altering local and regional hydrology. To explore these environmental consequences of urbanization this research would like to forecast the land-use change and assesses the long-term runoff water through hydrologic modeling. To know the detrimental effects of future disasters, especially drought, flood, and tropical storms, this research provided by a simulation technique, and based on two skenarios. First, simulation with a land-use change skenario. Second, simulation without a land-use change skenario. It provided by some parameters such as characteristics of catchments, land use, contour, river, soil, infiltration, and rainfall intensity. The objective of using different skenario is to know what kind of hydrological responses. Moreover, the outcomes would indicate that land use and climate change would likely be subjected to impacts the tremendous loss of life and damage due to excessive runoff and flooding. This is the primary watershed that affects the greater Jakarta urban zone, which has had increasingly severe flooding annually impacting and displacing hundreds of thousands of people. However, urbanization will considerably increase runoff water. Finally, the results of this research would have significant implications to support decision-makers, academia, and the wider public in preparing urban planning, water resources management, development of better regulations and their effective implementations. The techniques described in this proposed research can be used in other areas.